Konsiderasi Teknik Anestesi pada Crash Ponek Fetal Distress - Apsari, Ratih Kumala Fajar; Uyun, Yusmein; Adrin, Olga Elenska (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Neonatal and infants’ mortality rate in Indonesia is still high. Emergency case in comprehensive obstetric and neonatal emergency care is one of the causes related to high mortality rate in pregnancy and neonates. There is a thin line between true emergency which may need emergency surgery, previously known as crash-C-section and emergency that could be optimized before surgery is performed. A true emergency may need considerable anesthesia technique which could be done quickly yet also emphasizes on patient’s safety.